Psychometric characteristics of the Croatian and the Serbian versions of the oral health impact profile for edentulous subjects, with a pilot study on the dimensionality - Čelebić Asja; Stančić Ivica; Kovačić Ines; Popovac Aleksandra; Topić Jolanda; Mehulić Ketij; Elenčevski Sašo; Peršić Sanja (Sciendo, 2020)
The aim was to adapt the Croatian and the Serbian versions of the Oral Health Impact Profile for the edentulous population (OHIP-EDENT-CRO and OHIP-EDENT-SRB).